Identification of Sustainable Environmental Literacy Needs as A Basis for Developing SDGs-Based Instruments - Savitri, Erna Noor; Sudarmin, Sudarmin; Nuswowati, Murbangun; Saptono, Sigit (Universitas Negeri Semarang, 2025)
Sustainable environmental literacy is an important competency in supporting the achievement of the Sustainable Development Goals (SDGs), especially for prospective science teacher students. This study aims to identify the need for sustainable environmental literacy as a basis for developing measurement instruments that are relevant to the context of education and global environmental challenges. This study uses a descriptive approach by compiling indicators based on cognitive, affective, and psychomotor dimensions, and considering aspects of social awareness and real action. The results of the analysis show a gap between students' pro-environmental knowledge and attitudes and their actual behavior in everyday life. This finding emphasizes the importance of instruments that are able to describe environmental literacy conditions holistically to support transformative education and form agents of change who care about environmental sustainability.